Medicine and modernity: public health and medical care in nineteenth- and twentieth-century Germany - Cocks, Geoffrey; Berg, Manfred (Cambridge University Press, 1997)
This collection of essays addresses, in a comprehensive and critical fashion, fundamental issues in the history of medicine in modern Germany. The essays also investigate important continuities and discontinuities in German history, and between Germany and the West. The central focus is on the professionalisation of modern medicine and the medicalisation of modern society. The problem of Nazi Germany is addressed in many of the essays, partly because of its influence on the debate over the nature of modern German government and society in relation to Western social, political, and economic development. Other topics include: the place of hospitals in the early nineteenth century, various forms of Social Darwinism, the politics of state-run health insurance, the influence of eugenics, social control and 'shell shock' in World War I, sterilization and euthanasia, Nazi experimentation, the abortion debate, and the role of former Nazis in the postwar medical leadership
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Aufsatzsammlung; Geschichte 1800-1993; Sozialmedizin; Deutschland; Gesundheitspolitik; Gesundheitswesen